PENGARUH PENERAPAN PENDEKATAN RME TERINTEGRASI NILAI-NILAI KEARIFAN LOKAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Samsinar Samsinar; Imaludin Agus; Sri Anandari Safaria; Dedyerianto Dedyerianto; Halistin Halistin (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Mathematical communication ability is an important ability possessed by students. However, students' mathematical communication skills still tend to be low. An approach that can help students improve their mathematical communication skills is to use an integrated RME approach with local wisdom values which is also an effort to preserve local wisdom in Indonesia. This research is a quasi-experimental quantitative research. The sampling technique used simple random sampling. Class VII B is applied as the experimental class and VII C is applied as the control class. The data collection method consisted of a test of mathematical communication skills seen from the aspects of writing, drawing, and mathematical expression, as well as the teacher's observation sheet. The results of this study indicate that: The application of the integrated RME approach to local wisdom values has a better effect than the conventional approach on students' mathematical communication skills.